2010
DOI: 10.1371/journal.pgen.1000981
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of Variance per Genotype as a Tool to Identify Quantitative Trait Interaction Effects: A Report from the Women's Genome Health Study

Abstract: Testing for genetic effects on mean values of a quantitative trait has been a very successful strategy. However, most studies to date have not explored genetic effects on the variance of quantitative traits as a relevant consequence of genetic variation. In this report, we demonstrate that, under plausible scenarios of genetic interaction, the variance of a quantitative trait is expected to differ among the three possible genotypes of a biallelic SNP. Leveraging this observation with Levene's test of equality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
274
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 206 publications
(281 citation statements)
references
References 25 publications
6
274
1
Order By: Relevance
“…Recent theoretical work showed that the within-genotype variance of a quantitative trait varies when a nonadditive genetic interaction or epistasis is present (Pare et al 2010;Struchalin et al 2010). Alternatively, the variance of a quantitative trait may be from the result of the interaction between genetic variants additively associated with the mean of the quantitative trait.…”
Section: Partially Linked Snps Contribute To Variable Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent theoretical work showed that the within-genotype variance of a quantitative trait varies when a nonadditive genetic interaction or epistasis is present (Pare et al 2010;Struchalin et al 2010). Alternatively, the variance of a quantitative trait may be from the result of the interaction between genetic variants additively associated with the mean of the quantitative trait.…”
Section: Partially Linked Snps Contribute To Variable Gene Expressionmentioning
confidence: 99%
“…Through either epistatic or nonepistatic (e.g., additive and dominance) effects within or between loci, genetic interactions contribute to genotypic variance. Epistasis may increase the variance of a quantitative trait (Pare et al 2010;Ronnegard and Valdar 2012). However, it is extremely difficult to distinguish the contributions of epistatic or nonepistatic effects to variable expression of genes.…”
mentioning
confidence: 99%
“…N 0 , N 1, and N 2 represent the pooled genotype counts in the major allele homozygote, heterozygote, and minor allele homozygote group, respectively. framework of variance prioritization 4,11 , according to which the sample size, number of SNPs, MAF, and the proportion of variance explained by the interactions and the covariate influenced the statistical power of variance prioritization. Beyond allowing the implementation of variance prioritization to select SNPs for a meta-analysis of genetic interactions or environmental sensitivity, there are many other potential applications of the meta-analysis of Levene's test.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, an analysis of 21 799 individuals from the Women's Genome Health Study first identified SNPs with a genome-wide significant Levene's test P-value for C-reactive protein (rs12753193, P ¼ 8.0E-11) and soluble ICAM-1 (rs738409, P ¼ 1.9E-10; rs1799969, P ¼ 2.1E-09). 4 Although it is feasible to analyze the heterogeneity of variance in individually large studies, sufficient sample sizes for the detection of variants with small effects can only be practically reached through meta-analysis. Indeed, a recent report has associated an FTO variant (rs7202116) with the phenotypic variability of body mass index (BMI) (P ¼ 2.4E-10; N ¼ 131 233) in a meta-analysis using the squared residual as the response variable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation